2018
DOI: 10.1016/j.surfcoat.2018.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of structure and mechanical properties of hard yet fracture resistant W‐B‐C coatings with varying C/W ratio

Abstract: Preparation of coatings simultaneously exhibiting high hardness and enhanced fracture resistance is a hot topic, as nowadays used ceramic protective coatings show difficulties to cope with increased demands due to their inherent brittleness. Material exhibiting seemingly contradictory combination of mechanical properties-high hardness and moderate ductility enhancing the fracture resistance-was recently predicted by ab initio calculations in the crystalline X2BC system. The presented study is focussed on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 45 publications
(43 reference statements)
7
12
0
Order By: Relevance
“…The Er measured in our films follow the same trends previously described for hardness, see Fig. 8a and 8b, with the highest value of ~ 280 GPa for the film deposited with 10 sccm TMB at 500 o C and a lowest value of ~130 GPa for the film deposited at 900 o C. Similar as for the hardness, our Er ~ 280 GPa value is similar to the Er ~ 300 GPa reported by Debnárová et al [27] but lower than the ~ 450 GPa reported in the studies by Alishahi et al [26]. Furthermore, for W2C and WC1-x films containing 35 at.% C Palmquist et al [14] measured an E-moduli of ~ 450 GPa, i.e.…”
Section: Mechanical Propertiessupporting
confidence: 89%
See 2 more Smart Citations
“…The Er measured in our films follow the same trends previously described for hardness, see Fig. 8a and 8b, with the highest value of ~ 280 GPa for the film deposited with 10 sccm TMB at 500 o C and a lowest value of ~130 GPa for the film deposited at 900 o C. Similar as for the hardness, our Er ~ 280 GPa value is similar to the Er ~ 300 GPa reported by Debnárová et al [27] but lower than the ~ 450 GPa reported in the studies by Alishahi et al [26]. Furthermore, for W2C and WC1-x films containing 35 at.% C Palmquist et al [14] measured an E-moduli of ~ 450 GPa, i.e.…”
Section: Mechanical Propertiessupporting
confidence: 89%
“…3a, centered at 187.9 eV, are of low intensity for films deposited with 1 and 2.5 sccm TMB. This binding energy is identical to the measured B-W binding energy for W2B5 [34] and W-B-C films deposited by Alishahi et al [26], and close to the 188.1 eV reported by Liu et al for W-B-C films [25]. There is no indication of B-B or B-O bonding in the films as no B 1s peaks are visible at 189.4 eV [34] or ~192-193 [34], respectively.…”
Section: Composition and Chemical Bonding Structuresupporting
confidence: 86%
See 1 more Smart Citation
“…This can be seen in the center diffraction patterns in Figure 8a,b. However, the formation of short-range ordered structures in the X-ray amorphous coating such as those seen in the case of WBC coatings is possible [23,25].…”
Section: Morphology and Structurementioning
confidence: 99%
“…Later, an ab-initio modeling of similar materials was performed and it was reported that crystalline Ta 2 BC and W 2 BC in particular are also promising candidates for experimental synthesis owing to their calculated elastic properties indicating their simultaneous high stiffness and moderate ductility [13]. Although experimental studies of coating systems like Ti-B-C [14][15][16][17][18][19][20], Ta-B-C [21], Nb-B-C [22], and W-B-C [19,[23][24][25][26][27][28] potentially leading to the formation of the X 2 BC crystalline structure have been published, no formation of the ternary crystalline X 2 BC phase other than Mo 2 BC has ever been reported [11,13].…”
Section: Introductionmentioning
confidence: 99%